2018
DOI: 10.1186/s40359-018-0228-1
|View full text |Cite
|
Sign up to set email alerts
|

An empirical examination of the conceptualization of companion animals

Abstract: BackgroundThe extensive keeping of companion animals and the substantial monetary amount we spend on these animals indicate that they are highly valued. Although the benefits humans derive from keeping cats and dogs have been extensively studied, how we conceptualize these animals has received limited attention. How people conceptualize cats and dogs is important as it influences human behavior and the well-being of humans as well as animals. The objective of this paper was to examine the conceptual meaning of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…It has been shown that a bond with companion animals can fulfill the attachment criteria. Companion animals provide a secure base from which to explore, and provide a safe haven in times of stress (Kurdek, 2009;Zilcha-Mano et al, 2011;Julius et al, 2012;Meehan et al, 2017;Hoffmann et al, 2018). Humans not only seek closeness to a companion animal but they also enjoy their company (Enders-Slegers, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that a bond with companion animals can fulfill the attachment criteria. Companion animals provide a secure base from which to explore, and provide a safe haven in times of stress (Kurdek, 2009;Zilcha-Mano et al, 2011;Julius et al, 2012;Meehan et al, 2017;Hoffmann et al, 2018). Humans not only seek closeness to a companion animal but they also enjoy their company (Enders-Slegers, 2000).…”
Section: Introductionmentioning
confidence: 99%